LOSARTAN NORMALIZES BLOOD PRESSURE AND PREVENTS RENAL DAMAGE AND INFLAMMATION INDUCED BY FRUCTOSE OVERLOAD. L-DOPA/DOPAMINE INDEX AS A NEW POTENTIAL BIOMARKER OF RENAL DAMAGE. (June 2018) - Puyó, A.M.; Mikusic, N.L. Rukavina; Kouyoumdzian, N.M.; Del Mauro, J.S.; Cao, G.; Pandolfo, M.; Gironacci, M.M.; Toblli, J.E.; Fernández, B.E.; Choi, M.R.
Abstract : Objective: The renin angiotensin system (RAS) and the renal dopaminergic system (RDS) act as autocrine and paracrine systems to regulate renal sodium management and inflammation, and their alterations have been associated to hypertension and renal damage. Nearly 30–50% of hypertensive patients have insulin resistance (IR), which has a strong correlation to microalbuminuria. The aim of this study was to evaluate the effects of RAS blockade with losartan on blood pressure and renal damage in a model of IR produced by fructose overload (FO), and its association to changes in the RDS. Finally, we studied the urinary L-dopa/dopamine index as a potential biomarker of renal dysfunction. Design and method: Male Sprague Dawley rats were divided into: Control (C, tap water), FO (10% w/v of fructose solution), Losartan (L, 30 mg/kg/day in tap water), FO + L (30 mg/kg/day in fructose solution) groups for 4, 8 and 12 weeks. Systolic blood pressure (SBP) and metabolic parameters were measured. Urinary L-dopa and dopamine, diuresis, natriuresis and microalbuminuria were determined. Renal expression of D1 receptor (D1R), pro-inflammatory markers (IL-6, TNF-alpha, TGF-beta1, angiotensin II [Ang II]) and Na + , K + -ATPase expression and activity were measured. Results: Losartan prevented the increase in SBP and Na + , K + -ATPase activity and the reduction in natriuresis induced by FO from week 4 (p < 0.05). Increased L-dopa/dopamine index and decreased D1R expression in FO rats were prevented by losartan since week 4 (p < 0.05). The same pattern was observed for renal expression of Na + , K + -ATPase, IL-6, TNF-alpha and TGF-beta1 since week 8 (p < 0.05), with no changes in Ang II. FO was associated with the appearance of microalbuminuria at week 12, effect prevented by losartan (p < 0.001). Conclusions: These results provide the mechanisms by which a prohypertensive and proinflammatory system, such as RAS, downregulates another antihypertensive and antiinflammatory system such as RDS, establishing a positive feedback loop that leads to hypertension and kidney inflammation due to FO. Furthermore, we demonstrated the potential usefulness of the L-dopa/dopamine index as a biochemical marker of renal dysfunction, earlier than microalbuminuria, and as a predictor of treatment response and follow-up of hypertension and kidney damage.